2018
DOI: 10.1111/jvim.15049
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Plasma Fructosamine Concentration as a Hypoglycemic Biomarker during Early Lactation in Dairy Cattle

Abstract: BackgroundPlasma fructosamine concentration ([FRA]) is a widely used long term hyperglycemic biomarker in humans and dogs, but its clinical usefulness as a hypoglycemic biomarker in dairy cattle is uncertain.ObjectivesTo evaluate the relationship between plasma [FRA] and glucose concentration ([gluc]) as well as indices of energy balance during early lactation in dairy cattle, and to characterize the influence of plasma total protein concentration ([TP]) and albumin concentration ([albumin]) on [FRA].AnimalsCo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The study reported here was part of a larger study investigating the prediction of parturition and dystocia, and energy and calcium homeostasis in the periparturient period in Holstein-Friesian cows. Additional results have been published elsewhere (Megahed et al, 2015;Hiew et al, 2016;Megahed et al, 2017;Megahed et al, 2018a;Megahed et al, 2018b;Megahed et al, 2019).…”
Section: Methodsmentioning
confidence: 97%
“…The study reported here was part of a larger study investigating the prediction of parturition and dystocia, and energy and calcium homeostasis in the periparturient period in Holstein-Friesian cows. Additional results have been published elsewhere (Megahed et al, 2015;Hiew et al, 2016;Megahed et al, 2017;Megahed et al, 2018a;Megahed et al, 2018b;Megahed et al, 2019).…”
Section: Methodsmentioning
confidence: 97%
“…With respect to the measured metabolites, fructosamine concentrations were lower in the blood and glucose-6-phosphate was lower in milk in cows with high BoHV-6 scores. Circulating concentrations of fructosamine are thought to reflect the average plasma glucose concentration over the previous two-to-three weeks [ 52 ] and have been used to identify disturbances in glucose metabolism in a variety of species including sheep and cattle [ 53 ]. Within milk, glucose-6-phosphate reflects the nutrient availability and metabolic turnover in the mammary gland [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on blood fructosamine concentration in the first month of lactation showed a positive correlation with concentrations of plasma glucose and albumin. The plasma fructosamine level during the first 3-4 weeks of lactation was a predictor for the energy balance in the transition period (8). NEB was more influenced by DMI and inflammatory conditions than the high milk production (8).…”
Section: The Transition Periodmentioning
confidence: 96%
“…The plasma fructosamine level during the first 3-4 weeks of lactation was a predictor for the energy balance in the transition period (8). NEB was more influenced by DMI and inflammatory conditions than the high milk production (8). The cow must receive enough energy, protein, vitamins, and minerals for colostrum and milk production at a time when DMI is dropping (38).…”
Section: The Transition Periodmentioning
confidence: 99%